2022
DOI: 10.1109/tdei.2022.3157936
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Use of Vegetable Oil on the Mechanical Failure of the Cellulosic Insulation of Continuously Transposed Conductors in Power Transformers

Abstract: Natural esters have become of interest for the industry in recent years as dielectric liquids for power transformers, and many studies are focused on their dielectric and chemical properties, and on their influence in the degradation of the solid insulation due to ageing. However, very little is known about their impact on the evolution of the mechanical properties of the paper insulation, which are acknowledged to have a considerable influence in their overall performance and reliability during the operating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Besides, it can be inferred that a reduction in the formation of acids, which could be achieved by changing some operating conditions or using other dielectric liquids, would better preserve the compressive properties of high-density cellulosic components in power transformers in operation. In the future, it would be interesting to study the compressive mechanical response of high-density pressboard when using other dielectric liquids, as it has been reported that the use of vegetable oil better preserves the tensile mechanical properties of thin paper during ageing, see Oria et al (2022), but there is no information about the effects of using this oil on compressive properties of pressboard.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it can be inferred that a reduction in the formation of acids, which could be achieved by changing some operating conditions or using other dielectric liquids, would better preserve the compressive properties of high-density cellulosic components in power transformers in operation. In the future, it would be interesting to study the compressive mechanical response of high-density pressboard when using other dielectric liquids, as it has been reported that the use of vegetable oil better preserves the tensile mechanical properties of thin paper during ageing, see Oria et al (2022), but there is no information about the effects of using this oil on compressive properties of pressboard.…”
Section: Discussionmentioning
confidence: 99%
“… Refs. Years Proposed technique Contribution 42 2021 Regression modeling The study estimated DP utilizing the furfural marker at different oil-to-pressboard ratios and oil change statuses 43 2022 Artificial Neural Network (ANN) The study estimated furans by analyzing temperature, carbon dioxide, carbon monoxide, and moisture to estimate DP 44 2022 Empirical modeling The study estimated DP utilizing methanol concentrations obtained at low temperatures. The relative error was 7% 45 2023 ANFIS, Roger’s ratio approach A hybrid Rogers ratio technique-based ANFIS was proposed to detect transformer faults.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations carried out have shown that the temperatures reached in a transformer using esters could be similar, or even lower, to those reached with mineral oils in adapted winding designs [12], [13], [14] Some manufacturers apply special treatments to improve the viscosity or the oxidation stability of these alternative liquids [15]. The effect of the fluid used on the degradation of the solid insulation, measured by the control of the chemical [16], mechanical [17] or light techniques [18] after a thermal [19] or electrical [20] ageing process, have also been afforded. Researchers have demonstrated that the degradation suffered by the cellulosic materials is lower when the cooling fluid is a natural ester, derived from sunflower, rapeseed, soy or palm, instead of a mineral oil at similar conditions [16], [17], [19], [21], [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the fluid used on the degradation of the solid insulation, measured by the control of the chemical [16], mechanical [17] or light techniques [18] after a thermal [19] or electrical [20] ageing process, have also been afforded. Researchers have demonstrated that the degradation suffered by the cellulosic materials is lower when the cooling fluid is a natural ester, derived from sunflower, rapeseed, soy or palm, instead of a mineral oil at similar conditions [16], [17], [19], [21], [22], [23]. The levels of degradation depended on the specific oil and the conditions of the study, not all the natural esters protected the insulation from degradation in the same degree [19], [24], and other natural esters of different origin (corn, peanut, coconut or mustard) showed worst performance [25], [26], [27], [28] The results with synthetic esters reflects slightly lower degradation than with the mineral oils [19], [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation